Interactivities in music intelligent tutoring system - Phon-Amnuaisuk, S.; Keh-Siong , Chee (2005)
We report our work in progress in the area of music intelligent tutoring systems (MITS). We discuss the motivation behind the design of GUI that aim to support an interactive learning in the MITS environment. These interactivities include onscreen score editing and capturing student behaviours during tutorial sessions (e.g. feedbacks, queries, stream of action-events). In this report, we discuss our representation, then our design and finally present some interaction examples from our system.